2023
DOI: 10.1001/jamainternmed.2023.4764
|View full text |Cite
|
Sign up to set email alerts
|

Care Ecosystem Collaborative Model and Health Care Costs in Medicare Beneficiaries With Dementia

Elan L. Guterman,
Rachel E. Kiekhofer,
Andrew J. Wood
et al.

Abstract: ImportanceCollaborative dementia care programs are effective in addressing the needs of patients with dementia and their caregivers. However, attempts to consider effects on health care spending have been limited, leaving a critical gap in the conversation around value-based dementia care.ObjectiveTo determine the effect of participation in collaborative dementia care on total Medicare reimbursement costs compared with usual care.Design, Setting, and ParticipantsThis was a prespecified secondary analysis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 35 publications
(83 reference statements)
0
7
0
Order By: Relevance
“…GUIDE seeks to alleviate caregiver burden by providing unpaid caregivers with training, access to a 24/7 support line, and reimbursement of up to $2500 annually for respite services. This builds on previous evaluations of effective interventions to improve caregiver well-being …”
Section: Addressing Current Flaws In Dementia Carementioning
confidence: 99%
See 3 more Smart Citations
“…GUIDE seeks to alleviate caregiver burden by providing unpaid caregivers with training, access to a 24/7 support line, and reimbursement of up to $2500 annually for respite services. This builds on previous evaluations of effective interventions to improve caregiver well-being …”
Section: Addressing Current Flaws In Dementia Carementioning
confidence: 99%
“…The traditional, disease-based approach fails patients with dementia because of fragmented care and inadequate consideration of both the patient-caregiver unit and the social needs of patients. In contrast, comprehensive dementia care models use individualized care plans and prioritize longitudinal, team-based follow-up to achieve utilization-driven reductions in spending on beneficiaries with dementia . However, with substantial upfront fixed costs, these models are not tenable under the incentives of FFS.…”
Section: Addressing Current Flaws In Dementia Carementioning
confidence: 99%
See 2 more Smart Citations
“…As a second example, the Care Ecosystem — a collaborative, team‐based dementia care program utilizing telehealth that involved care navigators, advanced practice nurses, social workers and pharmacists — resulted in fewer ambulance rides, emergency department visits and hospitalizations and lower total cost of care compared with usual care. 756 , 757 A non‐academic health care delivery organization which adopted the Care Ecosystem found that the model can be successfully implemented and integrated into purely clinical settings. 758 With regard to cost savings, participation in the Care Ecosystem reduced the total cost of care by $3,290 from 1 to 6 months post‐enrollment and by $3,027 from 7 to 12 months post‐enrollment, corresponding to a mean monthly cost reduction of $526 across 12 months.…”
Section: Workforcementioning
confidence: 99%